Influence of low external magnetic field on electric field induced strain behavior of 9/70/30, 9/65/35 and 9/60/40 PLZT ceramics - Somwan S. (2017)
© 2016 Elsevier Ltd and Techna Group S.r.l. In this work, Pb 0.91 La 0.09 (Zr x Ti 1−x ) 0.9775 O 3 PLZT ceramics, where x =0.70, 0.65 and 0.60, were prepared by a solid-state mixed-oxide technique. Structural information was investigated by X-ray diffraction method. Electric field induced polarization and strain behavior of the PLZT ceramics under an influence of static magnetic field were measured by a Sawyer-Tower circuit in conjunction with Michelson interferometer at various static magnetic fields (0–30.7 mT). The results showed that the imposed magnetic field affected the polarization and induced strain behaviors in PLZT ceramics More interestingly, the imposed magnetic field showed more significant influence on the PLZT ceramic composition near morphotropic phase boundary (MPB), i.e. PLZT 9/65/35. The spontaneous polarization of 180° domain switching was seen to be suppressed by the applied magnetic field.